Synthesis and biological evaluation of Santacruzamate-A based analogues. Issue 24 (15th December 2017) - Randino, Rosario; Gazzerro, Patrizia; Mazitschek, Ralph; Rodriquez, Manuela
Graphical abstract: Abstract: Several derivatives of Santacruzamate-A, a natural product that is structurally related to SAHA, were synthesized to explore the potential of carbamates and oxalylamides as novel biasing element for targeting the catalytic site of zinc-dependent histone deacetylases (HDACs). An additional class of Santacruzamate-A derivatives was synthesized to investigate the influence of the cap group and the linker element on HDAC inhibitory activity. All compounds were evaluated in dose response for their in vitro cytotoxic activity in MTT assay in HCT116 cells. HDAC inhibitory activity was evaluated in vitro by western blot analysis for histone hyperacetylation assay and biochemically for representative human HDACs isoforms. Two novel compounds were identified to exhibit potent time dependent anti proliferative activity. However, unlike hydroxamic acid analogues, the tested Santacruzamate-A derivatives showed no noticeable HDAC inhibitory activity. The ethylcarbamate moiety as unusual zinc-binding group displayed no ability to coordinate the zinc ion and thus, presumably, was not able to reproduce known inhibitor-substrate zinc-binding group interactions with the HDAC catalytic site. This study confirmed that the accommodation of the zinc-binding group is deeply critical of the positioning of the linker and the projection of the cap group toward the different surface pockets of the enzyme.